(untitled) (Global Journal of Management and Business Research, 2022)
The world has been struck by the ultimate calamity of the COVID-19 pandemic, which has wreaked havoc on organisations, in particular because employees working in these organisations have been affected in terms of their emotional, cognitive, and psychological aspects, resulting in inefficiency in both their professional and personal lives, and ultimately acting as a disarray for the organization’s culture. In this rising economy with intense market pressures and stakeholders rising expectations, satrtups have been striving hard to ensure long term-viability with respect to new adaptations. The pandemic’s impact on these startups have highlighted the importance of adaptability and resilience in their workforce, expedited the transition to a new digital chevalier and emphasised the prominence of human resources in these historic times, predicting HR’s future significance and function following COVID-19. The study’s goal is to highlight the characteristics that can help these startups modify their systems before and after the epidemic, deploy remote engagement strategies while minimising risks, and increase productivity while refining their culture. This research paper analyzes recent startup changes that are necessary for the professionals in these startups to redefine remote engagement techniques, which functions as a driving force in employee transformation, resulting in an enabling change in their startup culture, which is inescapable in the future. This research paper analyzes recent startup changes that are necessary for HR professionals to redefine remote engagement techniques, which functions as a driving force in employee transformation, resulting in an enabling change in their startup culture, which is inescapable in the future.